Feasible fabrication of durable superhydrophobic SiO2 coatings with translucency and self-cleaning performance - Chenxiang Wang; Feng Tian; Xuefen Zhang (Materials Research Express, 2020)
In this work, a versatile strategy was proposed to fabricate translucent superhydrophobic coatings by spraying the suspension of modified SiO _2 /polydimethylsiloxane (PDMS) on various substrates. The wettability can be adjusted by changing the mass ratio of modified SiO _2 nanoparticles in the suspension. By optimizing the parameters in the spraying process, a superhydrophobic surface with a water contact angle of 164.1 ± 3.4° and a sliding angle of 4.2 ± 0.4° was achieved. As prepared translucent superhydrophobic SiO _2 /PDMS coatings show good mechanical durability, chemical stability, and self-cleaning performances.